Inisiasi Dan Aklimatisasi Tanaman Kayu Putih (Melaleuca cajuputi) Hasil Perbanyakan Secara in-Vitro Pada Dua Jenis Media Dengan Berbagai Konsentrasi Sitokinin - Waeniati Waeniati; Yusran Yusran; I Nengah Suwastika (Mitra Sains, 2015)
This research was aimed to determine the best based medium containing BAP in Melaleuca cajuputi propagation at the initiation stage, and to obtain the best growth of cajuputi plantlets during acclimatization stage. The experiment was arranged in completely randomized design, which consists of two experimental stage, cajuputi bud initiation and cajuputi plantlet acclimatization. At the initiation stage, the tested treatment were combination of based medium (WPM and MS) and Cytokinin (BAP). While at the acclimatization stage, plantlets from each treatment of initiation stage were grown in soil medium. This research was conducted over May to December 2014 at the Laboratory of Forest Biotechnology, Forestry Faculty Tadulako University. Data were analyzed by Analysis of Varian and the differences between treatments were determined by Duncan Multiple Range Test (DMRT). The outcome of this research showed that WPM based medium containing 0.7 ppm BAP had the best responses to the growth of cajuputi planlet (Melaleuca cajuputi) at the initiation stage. Application of Woody Plant Medium (WPM) based medium contained 0.7 ppm BAP at the initiation stage, give the optimal responses to the growth of Eucalyptus planlet (Melaleuca cajuputi) during the acclimatitation stage.